Peran Akuntansi Manajemen dalam Pengambilan Keputusan Strategis - Diah Tri Utami Putri (Asosiasi Dosen Akuntansi Indonesia, 2025)
Information about management accounting systems (MAS) is needed for high-quality decision-making in business. Therefore, MAS must be developed and organized properly. This study aims to analyze the role of management accounting in corporate strategic decision-making. The research methodology used is a Literature Case Study (library research) is a data collection technique that involves researching books, literature, records, and various reports related to the problems faced. This study concludes that the management accounting system is the organization's main source of information needed in managerial decision-making. Strategic management accounting is no longer just a provider of information, instead, they can participate as an integral member of the strategic decision-making team.